Potret Manusia Dalam Perspektif Psikologi Islam - Musripah, Musripah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
Humans as individual creatures and as social creatures, so that in living life can never be separated from the influence of their environment. The condition of a person's thinking cannot be separated from the influence of his environment in accordance with the development of cultural, economic, political, educational and geographical factors where he lives. Therefore, to better understand the portrait of man in terms of the perspective of Islamic psychology, it is necessary to understand the essence of man and the historical background of Islamic psychology. In line with these problems, the author analyzes and studies related to